Development of electrospun composite polymer fiber as sorbents for oil spill mitigation / Sigma Akter - Akter, Sigma (2023)
Research on polymers has grown exponentially in the purpose of oil spill removal from the water surface. It is very important to take immediate action to remove the oil from the water surface to reduce worldwide oil pollution. Materials with high porosity and mostly, superhydrophobic and oleophilic natures are the best candidates for this purpose. In this research, the Electrospinning method was used to synthesize the polystyrene (PS), polysulfone (PSF), and polyvinylidene fluoride (PVDF) which produced solvent-free fibers for the application of oil-spill removal. Different concentrations of solvents were used to produce electrospun fibers using N, N-Dimethylformamide (DMF). Moreover, DMF/THF and DMF/TCE solvent mixtures were used for PS and PSF respectively to identify the best solvent for fabrication and to minimise the dissolving time of the polymers. Viscosity and conductivity were measured for all the electrospun solutions to find the appropriate viscosity and conductivity for producing fibers. Composite polymer fibers were produced using PS/PSF and PS/PVDF polymer blending. For producing the composite polymer fibers only DMF was used to reduce the possibility of chemical degradation inside the polymer blending.